Penerapan Blended Learning Model berbantuan Video dalam Meningkatkan Hasil Belajar Geografi Kelas XI di MA. At Taufiq Singaraja - Hamimah, Siti; Astawa, Ida Bagus Made; Sarmita, I Made (Universitas Pendidikan Ganesha, 2025)
This study aims to analyze the implementation of the video-assisted Blended Learning Model in geography learning to improve student learning outcomes in MA. At Taufiq Singaraja and analyze student learning outcomes before and after the application of video-assisted Blended Learning Model in MA. At Taufiq Singaraja. This research method uses Classroom Action Research (CAR). The subjects in this study were a class XI geography teacher and 22 students in class XI. The result of the study found that the video-assisted Blended Learning Model implemented by the teacher in planning and implementation in cycle 1, namely: 81.15 and 88.1, and cycle 2, namely: 72.7 and 85.4. Furthermore, the average student geography learning outcomes inthe initial observation was 77.05, cycle 1 was 78.27. and cycle 2 was 80.45. Based on the results of research that has been done, there is a significant increase in student learning outcomes with the application of the Blended Learning Model to class XI at MA. At Taufiq Singaraja.